The Effect of School Principal’s Servant Leadership of Vocational Schools in Temanggung Regency - Bagas Dwi Pratomo; Zainal Arifin (International Journal of Applied Business and International Management, 2020)
This research aims to examine the effect off school principal's servant leadership, discipline, work motivation, and teacher’s commitment on the performance of vocational school teachers in Temanggung Regency. The findings show that (1) servant leadership has no significant positive effect on performance; (2) servant leadership has a significant positive effect on discipline by 25%, 18% on work motivation, and 20% on commitment; (3) discipline, work motivation, and commitment significantly have positive effect on performance by 71%; and (4) servant leadership has a significant positive effect on performance through discipline, work motivation, and commitment. Significant performance improvement is not influenced by servant leadership. However, servant leadership has a significant positive effect through mediation of discipline, work motivation, and commitment.